Pocket radar guide key radar facts, equations, and data - Curry, G. Richard (Scitech Publishing, 2010)
Annotation ThePocket Radar Guideis a concise collection of key radar facts and important radar data that provides you with necessary radar information when you are away from your office or references. It includes statements and comments on radar design, operation, and performance; equations describing the characteristics and performance of radar systems and their components; and tables with data on radar characteristics and key performance issues.It is intended to supplement other radar information sources by providing a pocket companion to refresh memory and provide details whenever you need them such as in meetings, while traveling, or in the field.
Keywords: Radar -- Handbooks, manuals, etc.; elektronické knihy; electronic books